Towards disentangling the classification of freshwater fish trypanosomes - Zhang, Peng; Liu, Jie; Yin, Xiao-Ming; Zhou, Jun-Yu; Lukeš, Julius; Lun, Zhao-Rong; Lai, De-Hua (Marine life science & technology, 2023)
UNLABELLED: Currently, new species of freshwater fish trypanosomes, which are economically important parasites, are being described based on subjectively selected features, i.e., their cell morphology and the host species. We have performed detailed phylogenetic and haplotype diversity analyses of all 18S rRNA genes available for freshwater fish trypanosomes, including the newly obtained sequences of Trypanosoma carassii and Trypanosoma danilewskyi. Based on a sequence similarity of 99.5%, we divide these trypanosomes into 15 operational taxonomic units, and propose three nominal scenarios for distinguishing T. carassii and other aquatic trypanosomes. We find evidences for the existence of a low number of freshwater fish trypanosomes, with T. carassii having the widest geographic and host ranges. Our analyses support the existence of an umbrella complex composed of T. carassii and two sister species. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s42995-023-00191-0.
Keywords: Freshwater fish trypanosomes; Phylogeny; 18S rRNA; Morphology